1973
DOI: 10.1007/bf02373017
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of visual traps for monitoring and control of populations ofRhagoletis cerasi L.

Abstract: The authors --members of the OILB working group on genetic control of the Europan cherry fruit fly, Rhagoletis cerasi L. --describe in this second report the development of a standard trap for the target species and its applications in the framework of the genetic control procedures in progress. The trap has increased the attractiveness for the flies about t00 times compared with the traditional bait traps and has proven its effectiveness in recent suppression programs in the field.(*) Second report of the OIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…Per re&mgle, Lemon Yellow and red vertical re&urgles each captured more R. pomonella with increasing size of rectangle from 15 X 20, 30 X 61, and 61 X 122 cm to 122 X 244 cm, the largest size tested (Table II). Per cm", the numbers on yelilow decreased with increasing rectangle size, a response similar 'to cherry i&x (RhagoZetis cerusi L.) cap&red 104 differem sizes 109 yellow rectangles in cherry trees (Prolkopy & Boller 1971, Russ et al 1973). The numbers on red, however, 'increased with increasing rectangle size per cm2.…”
Section: Resultsmentioning
confidence: 88%
“…Per re&mgle, Lemon Yellow and red vertical re&urgles each captured more R. pomonella with increasing size of rectangle from 15 X 20, 30 X 61, and 61 X 122 cm to 122 X 244 cm, the largest size tested (Table II). Per cm", the numbers on yelilow decreased with increasing rectangle size, a response similar 'to cherry i&x (RhagoZetis cerusi L.) cap&red 104 differem sizes 109 yellow rectangles in cherry trees (Prolkopy & Boller 1971, Russ et al 1973). The numbers on red, however, 'increased with increasing rectangle size per cm2.…”
Section: Resultsmentioning
confidence: 88%
“…Four new treatments (totaling six) were evaluated at this site. These were an unbaited three-dimensional cross-shaped Rebell trap (Swiss Federal Research Station, Wadswill, Switzerland) used extensively in Europe for monitoring the European cherry fruit ßy (Boller 1969, Russ et al 1973), a 9-cm-diameter red sphere (Great Lakes IPM, Vestaburg, MI) baited with 2.0 g of ammonium acetate and 0.5 g protein hydrolysate mixed into 13 g of Tangle-Trap (Liburd et al 1998), a 9-cm-diameter red sphere baited with aqueous ammonium solution containing 2.0 g of ammonium acetate in 4 ml of water, a modiÞed version of the Ladd trap (L & S trap) consisting of yellow background with a 9-cm-red hemisphere (the L & S trap was baited with 2.0 g of ammonium acetate and 0.5 g protein hydrolysate mixed into 16 g of Tangle-Trap).…”
Section: Methodsmentioning
confidence: 99%
“…In studies with the related European cherry fruit ßy, Rhagoletis cerasi L., Russ et al (1973) compared responses of R. cerasi to two and three-dimensional traps in replicated Þeld studies. He found that the response of R. cerasi to three-dimensional traps was superior compared with the two-dimensional sticky rectangular boards.…”
mentioning
confidence: 99%
“…For herbivores that respond positively to the visual stimulus of foliage reflectance, green pigments, and to a much greater extent yellow pigments (apparently constituting a supernormal foliage type stimulus), have proven valuable in management programs against various homopterans, beetles, and flies when incorporated into traps for monitoring (8,16,25,32 105,114,135) or direct control (35, 135,168). Populations of pest herbivores that respond positively to refi ectance patterns of other sorts of host plant structures, such as buds, blossoms, or bark, can likewise be effectively monitored by appropriately pigmented, refiectance-mimicking traps (128,157).…”
Section: Attractive St Imulimentioning
confidence: 99%